2020
DOI: 10.1097/bpb.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Current use of patient-reported outcomes in pediatric limb deformity surgery

Abstract: Patient-reported outcome (PRO) instruments are critical to evaluate the natural history of conditions and treatment effects, but have not been well studied in pediatric limb deformity. The goal of this study was to identify and assess the most commonly used PROs in pediatric limb deformity surgery across a representative sample of the recent orthopedic literature. A review was performed from 1 January 2016 to 31 December 2018 in five orthopedic journals previously identified as having the greatest impact:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Although a previous study found that no single PROM was universally used in pediatric LD, PODCI was the most commonly used. 9 Thus, PODCI questionnaires were administered to each age group. 10 The PODCI questionnaire was converted to a 5-point scale from its original 100-point scale by dividing all scores by a factor of 20 to allow for easier comparison with LD-EOSQ and LD-SRS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a previous study found that no single PROM was universally used in pediatric LD, PODCI was the most commonly used. 9 Thus, PODCI questionnaires were administered to each age group. 10 The PODCI questionnaire was converted to a 5-point scale from its original 100-point scale by dividing all scores by a factor of 20 to allow for easier comparison with LD-EOSQ and LD-SRS.…”
Section: Methodsmentioning
confidence: 99%
“…Although a previous study found that no single PROM was universally used in pediatric LD, PODCI was the most commonly used 9 . Thus, PODCI questionnaires were administered to each age group 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Amakoutou and Liu found that patient-reported outcome instruments currently used in pediatric limb deformity surgery are highly heterogeneous and are underutilized. The authors believed that future research is necessary to either validate a current patient-reported outcome measure in pediatric limb deformity or develop a new instrument using the pediatric PROMIS (Patient-Reported Outcomes Measurement Information System) or the PODCI (Pediatric Outcomes Data Collection Instrument) as a benchmark 25 . Hamilton et al developed a 62-question survey to determine the psychosocial factors that influenced the experiences of adolescents undergoing multiple limb-lengthening and reconstruction procedures 26 .…”
Section: Lower-extremity Deformitymentioning
confidence: 99%
“…The lack of patient-reported outcome scores and validation studies in limb deformity is a key obstacle, and a previous study identified the lack of consistency in patient-reported outcome measure use in pediatric limb deformity [1]. Fabricant et al [2] developed a system for adults by modifying the Scoliosis Research Society instrument for limb deformity, and recently, Griffiths et al [4] developed a pediatric-based patient-reported outcome measure [4].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%